2021
DOI: 10.1080/09637486.2021.1960958
|View full text |Cite
|
Sign up to set email alerts
|

A controlled human intervention trial to study protein quality by amino acid uptake kinetics with the novel Lemna protein concentrate as case study

Abstract: A human intervention trial was conducted to study amino acid uptake of the novel Lemna protein concentrate (LPC) in comparison to whey (WPC). The study was a cross-over, double-blind, controlled trial in which 12 healthy participants received 20 grams of LPC and WPC in randomised order. The LPC consumption resulted in a significant lower postprandial increase in almost all individual amino acids, total amino acid (TAA) and total essential amino acids (TEAA) compared to WPC based on area under the curve (AUC) c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 33 publications
0
13
0
Order By: Relevance
“…Proteomic analysis of the NF was performed by LC–MS/MS analysis and then a protein database matching the MS/MS spectra was performed for allergenic proteins using the ‘allergome’ protein sequence database. A match was found with Rubisco (ribulose‐1,5‐bisphosphate carboxylase), a very common protein present in commonly consumed leafy vegetables (Mes et al., 2022 ). The content of Rubisco in the NF was found to be very low compared to spinach based on sodium dodecyl sulphate–polyacrylamide gel electrophoresis (SDS–PAGE) analysis conducted by the applicant.…”
Section: Assessmentmentioning
confidence: 91%
See 1 more Smart Citation
“…Proteomic analysis of the NF was performed by LC–MS/MS analysis and then a protein database matching the MS/MS spectra was performed for allergenic proteins using the ‘allergome’ protein sequence database. A match was found with Rubisco (ribulose‐1,5‐bisphosphate carboxylase), a very common protein present in commonly consumed leafy vegetables (Mes et al., 2022 ). The content of Rubisco in the NF was found to be very low compared to spinach based on sodium dodecyl sulphate–polyacrylamide gel electrophoresis (SDS–PAGE) analysis conducted by the applicant.…”
Section: Assessmentmentioning
confidence: 91%
“…Postprandial areas under the curve for total amino acids and total indispensable amino acids from the NF as compared to the reference protein whey (set at 100%) were found to be 60.4% and 66.3%. However, interindividual variation was high as the values for total indispensable amino acids from the NF compared to the whey protein ranged from 18.2% to 94.2% (Mes et al., 2022 ).…”
Section: Assessmentmentioning
confidence: 99%
“…A large group of contaminants are the phenolic molecules, which bind to Rubisco and increase the protein’s resistance to degradation, and therefore its nutritional value is reduced ( Pedone et al , 1995 ; Alonso et al , 2000 ). Most recently, intervention trials have been carried out in which human subjects consumed protein concentrate derived from Lemna (duckweed) in order to better understand how leaf protein might be digested as part of the human diet ( Mes et al , 2022 ). This study observed no negative effects of consuming leaf protein concentrate, with less effect on glucose or insulin levels compared with whey protein concentrate, but it also showed lower uptake of amino acids compared with whey protein.…”
Section: Potential Of Rubisco As a Food Proteinmentioning
confidence: 99%
“…Thirdly, duckweed contains high amounts of protein (35-43% on dry weight basis), with a profile of essential amino acids that matches the requirements for humans better than most vegetable crops [5][6][7]. Protein concentrate of duckweed also has the potential to be well digestible [8]. Fourth, it is rich in micro and macro elements, vitamins, carotenoids and specific flavonoids and has a favorable fatty acid composition [9,10].…”
Section: Introductionmentioning
confidence: 99%